Extrapyramidal side effects of antipsychotics are linked to their association kinetics at dopamine D2 receptors - Sykes, David A.; Moore, Holly; Stott, Lisa; Holliday, Nicholas; Javitch, Jonathan A.; Lane, J. Robert; Charlton, Steven J. (Nature Publishing Group, 2017)
Atypical antipsychotic drugs (APDs) have been hypothesized to show reduced extrapyramidal side effects (EPS) due to their rapid dissociation from the dopamine D2 receptor. However, support for this hypothesis is limited to a relatively small number of observations made across several decades and under different experimental conditions. Here we show that association rates, but not dissociation rates, correlate with EPS. We measured the kinetic binding properties of a series of typical and atypical APDs in a novel time-resolved fluorescence resonance energy transfer assay, and correlated these properties with their EPS and prolactin-elevating liabilities at therapeutic doses. EPS are robustly predicted by a rebinding model that considers the microenvironment of postsynaptic D2 receptors and integrates association and dissociation rates to calculate the net rate of reversal of receptor blockade. Thus, optimizing binding kinetics at the D2 receptor may result in APDs with improved therapeutic profile.